Underachievement of Gifted Students in English-specialized 11th Grade Classroom, Nguyen Trai High-school, Hai Duong Province: A Case Study = Nghiên cứu trường hợp về hiện tượng học sinh có năng khiếu nhưng chưa phát huy hết thực lực lớp 11 anh, THPT Nguyễn Trãi, Hải Dương - Vu, Bao Chau (2020)
The research aims at students who have subsequent ability but continually achieve unsatisfying results in monthly tests issued by the school. As participants of this research, students stand the chance to reflect on their experience of studying English in an intense environment for gifted students. The researcher is most interested in looking at their characteristics; their self-perceived difficulties and what they think can make them study better